2019
DOI: 10.1126/science.aax5921
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-state–selective electron recombination studies suggest enhanced abundance of primordial HeH +

Abstract: The epoch of first star formation in the early Universe was dominated by simple atomic and molecular species consisting mainly of two elements: hydrogen and helium. Gaining insight into this constitutive era requires a thorough understanding of molecular reactivity under primordial conditions. We used a cryogenic ion storage ring combined with a merged electron beam to measure state-specific rate coefficients of dissociative recombination, a process by which electrons destroy molecular ions. We found a pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…Given the extreme conditions of temperature and pressure, the interstellar medium (ISM) is a perfect framework to find unconventional molecules that are unthinkable in the Earth's atmosphere. Such example is the noble gas (Ng) hydride cations, NgH + (Fortenberry, 2017 , 2019 ; Bovino and Galli, 2019 ; Novotný et al, 2019 ). The existence of these noble gas compounds is fascinating, as they are constituted by noble gases that are characterized by their high electronic stability, and in addition they are charged species with a long enough half-life time to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Given the extreme conditions of temperature and pressure, the interstellar medium (ISM) is a perfect framework to find unconventional molecules that are unthinkable in the Earth's atmosphere. Such example is the noble gas (Ng) hydride cations, NgH + (Fortenberry, 2017 , 2019 ; Bovino and Galli, 2019 ; Novotný et al, 2019 ). The existence of these noble gas compounds is fascinating, as they are constituted by noble gases that are characterized by their high electronic stability, and in addition they are charged species with a long enough half-life time to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present merged-beams experiment, together with the recent demonstration of a (near) single-quantum-state beam of molecular ions in the same apparatus [31], promise to open up a new era in the field of atomic and molecular collision physics. Worldwide there are three cryogenically cooled ion-beam storage rings in operation [27,33,34] where experiments with internally relaxed ions are performed [35]. Studies of single individual ion-ion interactions are, however, only possible in DESIREE.…”
Section: Introductionmentioning
confidence: 99%
“…A very broad distribution of initial states in the experiment could conceal distinct state-sensitive phenomena through the need to average over many initial quantum states when evaluating the model. The importance of experiments on internally cold ions was recently demonstrated through measurements of dissociativerecombination rates as functions of the rotational state in HeH + + e − reactions (all HeH + ions in the vibrational ground state v=0) at CSR [197]. It was then found that the rate is a strong function of the rotational excitation, which is in stark contrast to what has been assumed in earlier astrophysical models.…”
Section: Challenges and New Directionsmentioning
confidence: 96%